The influence of gender, career exposure and self-concept factors towards employability skills among students in entrepreneurial development and graduate marketability program - Mohd Puad, Mohd Hazwan; Ahmad Bakhtiar, Ain Nadzira (Faculty of Educational Studies, Universiti Putra Malaysia, 2019)
Statistics show that unemployment among university graduates is not influenced solely by their academic achievement but also influenced by their acquisition of employability skills. The acquisition of employability skills is critical to secure employment opportunities among undergraduate students. This study aimed to examine the level of employability skills, gender, career exposure, and self-concept factors among students who participate in the Entrepreneurship and Employability Development Program at Universiti Putra Malaysia. This study is a survey study and conducted by using the questionnaire instrument. The questionnaire was adapted and modified from the Malaysian Engineering Employability Skills Framework (MEES). Final year students of the Faculty of Agriculture, Universiti Putra Malaysia participating in the program were selected using a non-random sampling method. The data were analyzed descriptively and inferentially with IBM SPSS Statistics software. The findings depict that the level of employability skills of the students is at high level in terms of teamwork skills followed by competencies in discipline, competencies in application and practice, and communication. The mean of level of problem-solving and decision-making skills is slightly below the overall mean value. There were no significant differences in employability skills scores between men and women. Students with high career exposure tend to acquire employability skills. There is a positive and weak relationship between self-concept and employability skills. In conclusion, the university, the program and students need to play their role in enhancing the level of employability skills of students in order to produce high quality graduates and withstand future challenges in the industry.